'I can't remember a more depressing time but I don't blame anyone for that': remembering and commemorating the wartime internment of enemy aliens in Britain. (1st January 2019) - Pistol, Rachel
ABSTRACT: In October 2000, David Cesarani decried the unnecessary internment of refugees from Nazi Germany in Britain during the Second World War on the BBC Radio 4 programme Behind the Wire . Until the last few decades, little was known about the internment of enemy aliens by the British during the war. However, in recent years, novels such as David Baddiel's The Secret Purposes, published in 2004, and exhibitions such as 'Schwitters in Britain' at the Tate Britain in 2013, have introduced a wider audience to this oft-forgotten part of the British wartime narrative. Some of those interned in Britain were sent to Canada and Australia, which led to the greatest tragedy of the entire internment debacle, the sinking of the Arandora Star . The year 2015 marked the seventy-fifth anniversary of this tragedy, and the memory of those who were lost lives on in the British–Italian community. However, outside those affected by the Arandora Star disaster, little is commemorated or understood by the general public. Yet the legacy of the former internees is all around us. Who has not, on visiting the British Library, walked past former internee's Eduardo Paolozzi's statue of Newton? What connoisseur of classical music has not enjoyed the sound of the Amadeus Quartet, perhaps the only positive outcome of internment? Pistol's article will examine the memory of the camps and consider the differences between how internment has been remembered and commemorated by former internees and the general public.